Moderasi Beragama Sebagai Paradigma Pembelajaran PAI: Membangun Karakter Humanis Peserta Didik - M. Nuzulul Ulum; Muqowim (Chalim Journal of Teaching and Learning, 2026)
This study aims to analyze the implementation of religious moderation as a paradigm of Islamic Religious Education (PAI) learning in building the humanistic character of students at SMP Negeri 2 Pasir Sakti. This study employs a qualitative approach with a field research method through observation, interviews, and documentation involving the principal, PAI teachers, and students as informants. The findings reveal that the implementation of religious moderation is carried out through the integration of four main pillars, namely national commitment, tolerance, anti-violence, and accommodation of local culture in learning activities and school culture. These values have been proven to shape students’ humanistic character, as reflected in attitudes of mutual respect, empathy, and peaceful behavior. However, several challenges were identified, such as limited instructional time and differences in students’ understanding. Therefore, religious moderation as a paradigm of PAI learning plays a strategic role in creating an inclusive and civilized educational environment.